PERBEDAAN VARIASI SAMPAH SAWI DAN PEPAYA SEBAGAI PAKAN CACING TANAH (Lumbricus rubellus) TERHADAP KUALITAS VERMIKOMPOS - Nurcahyani; Ruyani, Aceng; Johan, Henny; Mayub, Afrizal; Parlindungan, Deni (Jurnal Tanah dan Sumberdaya Lahan, 2025)
The purpose of this study was to determine the NPK value, biomass increase, and pH as the effect of the use of variations in Chinese cabbage and papaya waste feed to reduce environmental pollution and also increase the benefits of organic waste, and organic vegetable and fruit waste has the potential to fertilize the soil. This study was conducted on July 22, 2024 to August 19, 2024 at the Sumber Belajar Ilmu Hayati Ruyani (Bengkulu) and used the RAL (Complete Randomized Design) research method. Data analysis was carried out using an analytical balance, pH paper, and NPK level testing carried out at the Soil Science Laboratory, University of Bengkulu on November 18, 2024 using the methods, namely Nitrogen (Kjeldahl or spectrophotometric method), Phosphorus (Sulfuric acid method followed by spectrophotometric method), Potassium (Extraction method followed by analysis using spectrophotometry). The results of the study showed that the highest NPK levels in sequence were Nitrogen (N) 2.05% in the 100% (Chinese cabbage) feed variation, Phosphorus (P) 0.58% in the 75% (papaya): 25% (Chinese cabbage) feed variation and potassium (K) 0.40% in the 50% (Chinese cabbage): 50% (papaya) feed variation. The highest biomass increase was obtained in the 100% (papaya) feed variation with a weight increase of 27.4g and the highest pH in the 100% (papaya) variation of 6.8 in the normal category. Based on the results of data analysis, it can be concluded that the addition of earthworms Lumbricus rubellus in making vermicompost can degrade Chinese cabbage and papaya waste into usable products, and the use of Chinese cabbage and papaya waste as feed in making vermicompost can increase NPK levels, Biomass and soil pH.